Ethics in business organizations in lima - Aristizábal Castañeda, Rayniero José (2020)
This essay presents a pragmatic reflection about the problems of firms, in Lima, as far as ethics is concerned, as they pursue their ordinary business affairs. The objective of this reflection is to raise an awareness, through three fronts, as far as the behavior of the owners of these organizations, within the social framework in which they coexist: the first front is ethics for a businessperson; the second, is the art of doing business and its organizational culture; and, finally, as a third front, the companies focused on the common good.